Dietary intake of anthocyanins and risk of cardiovascular disease: A systematic review and meta-analysis of prospective cohort studies. Issue 18 (11th October 2019) - Kimble, Rachel; Keane, Karen M.; Lodge, John K.; Howatson, Glyn
Abstract: Accumulating evidence suggests flavonoid intake is associated with reduced risk of non-communicable diseases. We aimed to systematically determine and quantify the potential association between dietary anthocyanin intake and risk of cardiovascular diseases (CVD). A systematic literature search of studies reporting anthocyanin intake and risk of fatal or nonfatal CVD was performed using SCOPUS, MEDLINE, CINAHL and Cochrane Library. The relative risk (RR) or hazard ratio (HR) of highest category of anthocyanin foods were pooled in a random-effects meta-analysis. Subgroup analysis were conducted to determine possible sources of heterogeneity. The meta-analysis suggested intake of dietary anthocyanins and reduced risk of CHD (RR = 0.91, 95% CI: 0.83, 0.99; I 2  = 12.0, P h  = 0.337) and CVD mortality (RR = 0.92, 95% CI: 0.87, 0.97; I 2  = 0.0, P h  = 0.584). However, there was no relationship between the intake of these compounds and reduced risk of MI, stroke or total CVD. Subgroup analysis determined reduced risk of CHD and CVD mortality was more prominent for anthocyanidin intake, as opposed to anthocyanin or berries. Our systematic review and meta-analysis provides evidence that anthocyanins, specifically anthocyanidins, reduce the risk of CHD and CVD mortality. Further randomized controlled trials on anthocyanin intake and CVD risk factors are needed to support these findings.